Uma abordagem heurística para o problema de otimização de distrito postal - Fiório, Rafael Carpanedo (2006)
This study proposes a strategia solution for the optimized construction of postal districts. Postal District is a set of segments of publics areas connecteds. Given a locality composed of uncounted segments of publics areas, this study proposes an arrangement of connects subgroups of publics areas with the goal of composing a postal district. The strategy is to transform the system of public areas of a place in a graph and from this graph, to extract their respective cyclical subgraphs that are understood as atomics entities. Those atomics entities are submited by an assembly process until compose a group of postal districts. The methodology here presented divides the study in two different phases: the first one understands the process of obtaining of the cyclical subgraphs; and the second one is understood as the assembly process of postal district The process of obtaining of cyclical subgraph consists in the obtaining of the hull convex of the graph and subsequent extracting up the cyclical subgraphs tangent to edge of that. That is, in a sequential way, in other words, it is determined the first convex hull of the graph and extract up their respective tangent subgraphs; it is determined the second convex hull and extract up their subgraphs and so forth. The study of determination of the convex hull and extracting of the cyclical subgraphs is done through operations of the computational geometry. The process of construction of the postal districts is given through the clustering of the cyclicals subgraphs, using as a tool the meta- heuristic Simulated Annealing. The Chinese Postman's Problem and Capacited Chinese Postman's Problem are formulations support for the present study. The main objective of the study is to obtain, in a fast and efficient way the optimized postal district, with smaller unproductive course possible, offering agility for the process of domiciliary distribution of postal objects.